2003
DOI: 10.1038/sj.onc.1207004
|View full text |Cite
|
Sign up to set email alerts
|

Role of the TRAIL/APO2-L death receptors in chlorambucil- and fludarabine-induced apoptosis in chronic lymphocytic leukemia

Abstract: The standard treatments for chronic lymphocytic leukemia (CLL) include the alkylating agent chlorambucil (CLB) and the nucleoside analog fludarabine (F-ara-AMP, Flu). Tumor necrosis factor-related apoptosisinducing ligand (TRAIL) is a death receptor ligand that induces apoptosis preferentially in tumors. However, CLL cells seem to be resistant to TRAIL-induced apoptosis. The TRAIL apoptotic signaling pathway has also been implicated in genotoxin-induced apoptosis through upregulation of TRAIL death receptors D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
3

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 47 publications
3
40
3
Order By: Relevance
“…In oral cancer cells, p53 is frequently inactivated. In some cell types, DR5 is a downstream target of p53 (32,33). Some conventional chemotherapeutic drugs, including etoposide or doxorubicin, can induce DR5 expression and enhance TRAILinduced apoptosis in a p53-dependent manner in certain cancer cell types such as lung cancer and lymphocytic leukemia cells (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…In oral cancer cells, p53 is frequently inactivated. In some cell types, DR5 is a downstream target of p53 (32,33). Some conventional chemotherapeutic drugs, including etoposide or doxorubicin, can induce DR5 expression and enhance TRAILinduced apoptosis in a p53-dependent manner in certain cancer cell types such as lung cancer and lymphocytic leukemia cells (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…88,107,108 There was initially hope that treatment of CLL cells with TRAIL might by itself induce apoptosis. Previous studies, however, not only demonstrated that CLL cells are resistant to the induction of apoptosis by TRAIL, 88,107 but also suggested that recruitment of FADD and cleavage of caspase 8 is low in CLL isolates compared to the Jurkat T-cell leukemia line.…”
Section: Preclinical Studies Of Trail In Cllmentioning
confidence: 99%
“…88,107,108 There was initially hope that treatment of CLL cells with TRAIL might by itself induce apoptosis. Previous studies, however, not only demonstrated that CLL cells are resistant to the induction of apoptosis by TRAIL, 88,107 but also suggested that recruitment of FADD and cleavage of caspase 8 is low in CLL isolates compared to the Jurkat T-cell leukemia line. 107 In a subsequent study, MacFarlane and co-workers also showed that the HDAC inhibitors depsipeptide and trichostatin A, two examples of a promising new class of anticancer agents undergoing extensive preclinical and clinical investigation, [109][110][111][112] are unable to induce apoptosis in CLL cells by themselves, but nonetheless sensitize CLL cells to TRAIL.…”
Section: Preclinical Studies Of Trail In Cllmentioning
confidence: 99%
See 2 more Smart Citations